If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -2x = -3x + 9 Reorder the terms: 6 + -2x = 9 + -3x Solving 6 + -2x = 9 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 6 + -2x + 3x = 9 + -3x + 3x Combine like terms: -2x + 3x = 1x 6 + 1x = 9 + -3x + 3x Combine like terms: -3x + 3x = 0 6 + 1x = 9 + 0 6 + 1x = 9 Add '-6' to each side of the equation. 6 + -6 + 1x = 9 + -6 Combine like terms: 6 + -6 = 0 0 + 1x = 9 + -6 1x = 9 + -6 Combine like terms: 9 + -6 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| 14x^2-121=0 | | 500=(2*w)*4*w | | 56x^2+15x+1=0 | | 2+10+4=14+2 | | 4(3x+3)+3(2x+1)=4x+43 | | 4(t+16)+t=109 | | (3+4i)+(6+7i)= | | 66.33= | | -4c+3=8-y | | 5x-2(x+5)=-37 | | 3/5x-2=-14 | | 2X-3(3-6X)=-24 | | B^2+28B+c=0 | | -6.3(-0.03)= | | -1/5(d-5)=9 | | -1(6-6x)=10+4x | | 2/7x-9/7=5/7 | | 1/2*1/5= | | 10times-3= | | 8x-12x-18=27 | | ??+??=21 | | 4p+10=50 | | 2B-2C=12 | | 4g^2=12g | | -15(-6)= | | x^2+36x+60= | | 2(x-4)-11=2x-19 | | r+(s+2r)= | | 9999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999+11111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111122222222222222222222222222222222222222222222222=k | | 4k-7(4k+3)=-189 | | 2x^2+6x=5.625 | | 9999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999999+1111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111112222222222222222222222222222222 |